A self-assembled albumin based multiple drug delivery nanosystem to overcome multidrug resistance. Issue 9 (23rd December 2014) - Chen, Bin; Wu, Cong; Zhuo, Ren-Xi; Cheng, Si-Xue
Abstract : A self-assembled nano-sized albumin based drug delivery system co-loaded with an anti-tumor drug and a drug resistance inhibitor has promising applications in overcoming multidrug resistance (MDR). Abstract : A facile strategy to construct a multiple drug delivery platform to overcome multidrug resistance (MDR) was developed. A nano-sized albumin based drug delivery system with the capability to simultaneously entrap different drugs was prepared by self-assembly. An anti-tumor drug (doxorubicin, DOX) and a drug resistance inhibitor (verapamil, VER) were efficiently co-loaded in bovine serum albumin (BSA) to obtain DOX/VER/BSA nanoparticles. The interactions between the drugs (DOX and VER) and BSA were studied by fluorescence spectroscopy. The size and zeta potential of the nanoparticles were determined by dynamic light scattering (DLS). The morphology of the nanoparticles was observed by transmission electron microscopy (TEM). DOX/VER/BSA nanoparticles exhibited a spherical shape with a mean size around 50 nm. The in vitro tumor cell inhibition efficiency of the nanoparticles was evaluated in HCT-15 cells with a moderate overexpression of P-glycoprotein (P-gp) as compared with 293T cells without overexpression of of P-gp. As compared with free DOX and DOX/BSA nanoparticles, DOX/VER/BSA nanoparticles exhibited a stronger tumor cell inhibitory effect because of the enhanced intracellular DOX concentration caused by the efflux pump inhibition of VER. These results indicated that the BSA based multiple drug delivery platform could be promising for drug delivery for overcoming multidrug resistance in cancer treatments.